Efeito do estádio de maturação sobre o consumo e digestibilidade aparente da matéria seca de três gramíneas tropicais - Coelho da Silva, J F; Gomide, J A (Revista Ceres, 2025)
The effect of stage of maturity upon dry matter consumptionand digestibility was studied with three tropical grasses, gordura grass (Melinis minutiflora Beauv.), pangola grass (Di- gitaria pentzii Stent.) and sempre-verde grass (Planicum ma- ximum Jacq.). Male sheep in matabolism cages, were used for this experiment.